The legal nature of presentation and maintenance by the prosecutor of the civil suit in criminal proceedings - Лапкін, А. В. (Problems of legality, 2013)
General provisions of presentation and maintenance by the prosecutor of the civil suit in criminal proceedings are considered. The functional orientation of activity of the prosecutor in this direction is characterized. Gaps and shortcomings of its legislative settlement and practical realization come to light, specific proposals on their elimination are given.